Cochlear implantation in osteogenesis imperfecta in India: a case report - Kumar, Rajesh; Chaudhary, Ashvanee Kumar; Kumar, Sunil; Singh, Vishwambhar; Abinashi, Ashutosh A.; Das, Subhadeep (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
A 25 years old male patient with osteogenesis imperfecta presented with bilateral profound hearing loss, not benefitted with hearing aid. Cochlear implantation of 12 channel intracochlear implant was done successfully, intracochlear insertion of the 12 electrodes resulted in hearing improvement of 80 dB at frequency 250 Hz to 4 KHz. The patient complained of facial twitching on first visit after switching on speech processer device, reducing the current level at the electrode 6 abolished the non-acoustic nerve excitation with preservation of acoustic performances. Osteogenesis imperfecta patient may involve a risk for non-acoustic nerve activation in cochlear implant patients possibly resulting from a decrease impedance to current spread, it happens because of abnormal bone tissue. Non acoustic nerve activation can be overcome by modification in mapping.